Timing of antibiotic administration and lactate measurement in septic shock patients: a comparison between hospital wards and the emergency department - Vattanavanit, Veerapong (Infect Drug Resist, 2018)
BACKGROUND: The timing of intravenous antibiotic administration and lactate measurement is associated with survival of septic shock patients. Septic shock patients were admitted to the medical intensive care unit (MICU) from 2 major sources: hospital ward and emergency department (ED). This study aimed to compare the timing of antibiotic administration and lactate measurement between hospital wards and the ED. PATIENTS AND METHODS: Medical data were collected from adult patients admitted to the MICU with septic shock from January 2015 to December 2016. “Time Zero” was defined as the time of diagnosis of sepsis. The associations between the times and risk-adjusted 28-day mortality were assessed. RESULTS: In total, 150 septic shock patients were admitted to the MICU. The median time interval (hour [h] interquartile range [IQR]) from time zero to antibiotic administration was higher in patients from the hospital wards compared to those from the ED (4.84 [3.5–8.11] vs 2.04 [1.37–3.54], P<0.01), but the lactate level measurement time interval (h [IQR]) from time zero was not different between the hospital wards and the ED (1.6 [0.2–2.7] vs 1.6 [0.9–3.0], P=0.85). In multivariate analysis, higher risk-adjusted 28-day mortality was associated with antibiotic monotherapy (odds ratio [OR]: 19.3, 95% confidence interval [CI]: 2.4–153.1, P<0.01) and admission during the weekends (OR: 24.4, 95% CI: 2.9–199.8, P<0.01). CONCLUSION: Antibiotic administration in septic shock patients from the hospital wards took longer, and there was also less appropriate antibiotic prescriptions seen in this group compared with those admitted from the ED. However, neither the timing of antibiotic administration nor lactate measurement was associated with mortality.